The Relationship of Managerial Competence and Interpersonal Communication with The Performance of Head of PAUD Se-Jatiasih District, Bekasi City - Ernawati; Baharuddin (Proceeding International Conference on Education, 2023)
This study aims to determine the relationship between the managerial competence of the performance of PAUD heads in Jatiasih District, Bekasi City, then to determine the relationship of interpersonal communication to the performance of PAUD heads in Jatiasih District, Bekasi City and to determine the relationship between managerial competence and interpersonal communication on the performance of PAUD heads in Jatiasih District, Bekasi City. This study uses a quantitative approach, namely research that emphasizes its analysis on numerical data (numbers) processed by statistical methods. With the quantitative method, the significance of the relationship between the variables studied will be obtained. The relationship between Managerial Competence and Interpersonal Communication together influences Principal Performance by 79%, and 21% is influenced by other variables not examined. The significant value of the Managerial Competency variable is 0.005 or sig <0.05, which means that Ho is rejected and Hi is accepted. This shows that Managerial Competence has a partial effect on the Performance of PAUD Principals in the Jatiasih District, Bekasi City. Whereas the Interpersonal Communication variable shows a significant value of 0.000 or sig <0.05, which means that Ho is rejected and Hi is accepted. This shows that Interpersonal Communication has a partial effect on the performance of PAUD Principals in the Jatiasih District, Bekasi City. Because good Managerial Competence and Interpersonal Communication will improve quality and affect Principal Performance. Without good school principal performance it is impossible for the school to develop in accordance with the existing vision and mission. By conducting research as a scientific way to obtain data with a specific purpose and specific uses.